Common Adverse Effects of Anti-TNF Agents on Gestation - Zacharias Fasoulakis; Panagiotis Antsaklis; Nikolaos Galanopoulos; Emmanuel Kontomanolis (Obstetrics and Gynecology International)
Autoimmune disease has affected up to 50 million Americans, according to the American Autoimmune Related Diseases Association (AARDA) and 75 percent of those affected are women. These inflammatory diseases have variable activity and a lot of women will have to undergo major therapies during and after pregnancy. Many of the women suffering from these disease will improve during gestation. However a lot of women will require continuation of disease-modifying therapies (i.e., biological therapies) throughout pregnancy and post-partum involving many risks. In the past decade all gaze turned to biological therapies, as an attempt, to obtain even more effective medications in order to suppress the exacerbation of autoimmune disease, even at the most unfit circumstances such as pregnancy. The results are both satisfying and promising since increasingly proven thoughts prevail on making anti-TNF agents first-line medications, clearing up the limited knowledge over human influence. The purpose of this review is to summarize the results of the reports with the highest and representative range of patients of the last decade involving the use of anti-TNF agents during pregnancy.